Studi Literature Riview : Pemanfaatan Sofware Matematika Geogebra Sebagai Media Belajar Untuk Mengetahui Kemampuan Komputasi Peserta Didik - Zulayli Syahrani; Yahfizham Yahfizham (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
To improve quality human resources, it must be addressed at the educational level. One effort that can be made so that the learning process can improve in this era of very rapid technology is by using teaching media in mathematics learning. One example is the use if geogebra which can help solve given mathematical problems. The aim of this research is to clarify the benefits if Geogebra as a mathematics teaching medium. The results of this research show that there are many benefits from using Geogebra and can determine the extent of students' computing understanding.